HOW TO AVEID PL - Nargiza Botirovna Abdullayeva (TADQIQOTLAR, 2026)
Annotation This  article  discusses  the  concept  of  plagiarism,  its  negative  impact  on  the educational process, and effective ways to avoid it. The importance of independent thinking, proper use of sources, citation rules, and paraphrasing techniques in writing scientific papers and articles is also analyzed. In addition, the article presents modern methods and recommendations for preventing plagiarism.